2015
DOI: 10.1080/14498596.2015.1004653
|View full text |Cite
|
Sign up to set email alerts
|

Application of a fuzzy inference system to mapping prospectivity for the Chahfiroozeh copper deposit, Kerman, Iran

Abstract: Mineral Potential Mapping (MPM) is usually regarded as a complex procedure. In modelling such a procedure, aspects such as the multiplicity of factors, fuzziness in the qualitative and quantitative data, and diverse experts' viewpoints need to be considered. To respond to these requirements, in this research, a methodology is proposed on the basis of the Fuzzy Inference System (FIS) and relations. The method is tested on the data of the Chah Firoozeh prospect, Kerman, Iran, to map the porphyry copper prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Number of study areas References Sudan 1 [39], [40], [41] Namibia 1 [42], [43], [44] Argentina 4 [45], [46], [47] , [48], [49], [50], [51], [52], [53], [54], [55], [56] Iran 4 [57], [58], [59], [60], [61], [62], [63], [64], [65] , [66], [67], [68], [69], [70] Pakistan 3 [71], [72], [73], [74], [75], [76] , [77], USA 5 [71], [78], [79], [80], [81], [82], [83] [84], [85], [86], [87] , [88], [89]…”
Section: Regionmentioning
confidence: 99%
“…Number of study areas References Sudan 1 [39], [40], [41] Namibia 1 [42], [43], [44] Argentina 4 [45], [46], [47] , [48], [49], [50], [51], [52], [53], [54], [55], [56] Iran 4 [57], [58], [59], [60], [61], [62], [63], [64], [65] , [66], [67], [68], [69], [70] Pakistan 3 [71], [72], [73], [74], [75], [76] , [77], USA 5 [71], [78], [79], [80], [81], [82], [83] [84], [85], [86], [87] , [88], [89]…”
Section: Regionmentioning
confidence: 99%
“…Xu et al (2011) apply a fuzzy relation model to analyze the amount of coal gas in mines; this model was applied to predict the spatial distribution of coal gas content in the air. In Moghadam et al (2015) a framework based on fuzzy relations and a fuzzy inference system is implemented to construct mineral potential maps.…”
Section: Related Workmentioning
confidence: 99%
“…The membership function of each class is shown below in Figure 1. The figure presents an overview of the seven individual membership functions which are mathematically specified in Equations ( 4)- (10). Some researchers believe that the use of the Mamdani and Sugeno methods yields the same results [64,65].…”
Section: Variable Range Debt-to-equity Ratiomentioning
confidence: 99%
“…The results indicated that these sets of constraints lead to similar constraint categories with output fuzzy trained systems. Moghadam et al [10] used the FIS method to map the model. They found that a fuzzy inference system could be helpful in this type of research.…”
Section: Introductionmentioning
confidence: 99%